Pengaruh Literasi Keuangan dan Literasi Pajak terhadap Pengelolaan Keuangan UMKM : (Studi Kasus di UMKM Mitra Mandiri Kabupaten Brebes) - Rena Widayanti; Dumadi Dumadi; Mohamad Badrun Zaman; Roni Roni (GEMILANG: Jurnal Manajemen dan Akuntansi, 2025)
This study aims to identify and analyze the influence of financial literacy on financial management, tax literacy on financial management, as well as the simultaneous influence of financial literacy and tax literacy on financial management in UMKM Mitra Mandiri, Brebes Regency. The study population consisted of 120 individuals, and the sample was determined using the Slovin formula with an incidental sampling technique, resulting in 92 respondents. Primary data were obtained from respondents’ questionnaire answers. Hypothesis testing was conducted using SPSS 25. The theoretical foundation employed includes the Theory of Planned Behavior (TPB), financial management in MSMEs, financial literacy, and tax literacy. The results indicate that both financial literacy and tax literacy have a positive and significant influence on the dependent variable, financial management, whether partially or simultaneously, in UMKM Mitra Mandiri, Brebes Regency.